Development of curative therapies for sickle cell disease - Tanhehco, Yvette C.; Nathu, Ghazala; Vasovic, Ljiljana V. (Frontiers in Medicine, 2022)
Recent advances in managing Sickle Cell Disease (SCD) significantly improved patient survival and quality of life. Disease-modifying drug therapies such as hydroxyurea, L-glutamine, voxelotor, and crizanlizumab reduce pain crises and severe complications. Allogeneic hematopoietic stem cell transplantation using matched-sibling donors is currently the only standard curative option; however, only a small proportion of patients have such donors. Cord blood and haploidentical transplantation with a modified conditioning regimen have expanded the allogeneic donor pool, making the therapy available to more patients. Gene therapy is a promising cure that is currently undergoing clinical trials and different approaches have demonstrated efficacy. Multidisciplinary expertise is needed in developing the best treatment strategy for patients with SCD.